2015
DOI: 10.5897/ajmr2014.7210
|View full text |Cite
|
Sign up to set email alerts
|

Frequent carriage of invasive Salmonellae amongst patients infected with schistosomiasis in Sudan

Abstract: Bacteria-parasite association has been documented as a factor that is responsible for continued and prolonged bacterial infection, such as typhoid and paratyphoid fever in schistosomiasis patients. This work aimed to determine the presence of typhoid and paratyphoid Salmonella among schistosomiasis patients and to evaluate the efficacy of Widal test on such population. A cross sectional descriptive study was conducted between November 2005 and May 2006 in Managil region, Gezira State, Sudan. A total of 203 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Recent studies (since 2000) assessing non-typhoidal Salmonella carriers in sub-Saharan Africa are rare. Most of them addressed risk groups such as food handlers (Feglo et al, 2004;Smith et al, 2008;Addis et al, 2011;Misganaw and Williams, 2013;Bradbury et al, 2015), Schistosoma-infected individuals (Mohager et al, 2014;Salem et al, 2015;Mbuyi-Kalonji et al, 2020), or convalescent patients (Nkuo-Akenji et al, 2001), and none of them assessed sequence type or relatedness with clinical isolates.…”
Section: Comparison With Proportions Of Ints Carriers In Sub-saharan ...mentioning
confidence: 99%
“…Recent studies (since 2000) assessing non-typhoidal Salmonella carriers in sub-Saharan Africa are rare. Most of them addressed risk groups such as food handlers (Feglo et al, 2004;Smith et al, 2008;Addis et al, 2011;Misganaw and Williams, 2013;Bradbury et al, 2015), Schistosoma-infected individuals (Mohager et al, 2014;Salem et al, 2015;Mbuyi-Kalonji et al, 2020), or convalescent patients (Nkuo-Akenji et al, 2001), and none of them assessed sequence type or relatedness with clinical isolates.…”
Section: Comparison With Proportions Of Ints Carriers In Sub-saharan ...mentioning
confidence: 99%
“…According to Hsiao et al (2016), a symbiotic relationship exists between some bacterial strains and schistosomes which make dual infection particularly difficult to diagnose and treat. Studies in Nigeria, Sudan and the Democratic Republic of Congo have also unearthed a direct relationship between co-infection of Salmonella and either S. haematobium or S. mansoni (Ige and Agbo, 2018; Abdo et al, 2015;Mbuyi-Kalonji et al, 2020). Observations from the studies of Hsiao et al (2016), and Barnhill et al (2011), also revealed that adult schistosomes confer a form of protection to co-contaminant bacteria, enabling them to evade antibiotic therapy, thus prolonging their course and facilitating antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%